2022
DOI: 10.3201/eid2813.212352
|View full text |Cite
|
Sign up to set email alerts
|

Infection Prevention and Control Initiatives to Prevent Healthcare-Associated Transmission of SARS-CoV-2, East Africa

Abstract: The coronavirus disease pandemic has highlighted the need to establish and maintain strong infection prevention and control (IPC) practices, not only to prevent healthcare-associated transmission of SARS-CoV-2 to healthcare workers and patients but also to prevent disruptions of essential healthcare services. In East Africa, where basic IPC capacity in healthcare facilities is limited, the US Centers for Disease Control and Prevention (CDC) supported rapid IPC capacity building in healthcare facilities in 4 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Among the twelve studies analyzed [33][34][35][36][37][38][39][40][41][42][43][44], in the risk of bias assessment of the included studies, varying degrees of bias risk are observed, reflecting the diversity of study designs (Figure 2). Several studies, such as Lee et al ( 2022 2021) inherently exhibit some concerns regarding randomization but generally show low risk across other bias domains [38].…”
Section: The Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the twelve studies analyzed [33][34][35][36][37][38][39][40][41][42][43][44], in the risk of bias assessment of the included studies, varying degrees of bias risk are observed, reflecting the diversity of study designs (Figure 2). Several studies, such as Lee et al ( 2022 2021) inherently exhibit some concerns regarding randomization but generally show low risk across other bias domains [38].…”
Section: The Quality Assessmentmentioning
confidence: 99%
“…Several studies underscore the significance of robust infection prevention and control (IPC) programs, especially in the context of emerging infectious diseases like COVID-19. Saadeh et al (2022) [43] and Gomes et al (2022) [35] emphasize the need for improvements in IPC, including water, sanitation, and hygiene (WASH) practices, to protect both patients and healthcare workers. Furthermore, Talaat et al ( 2016) [34] and Hamam et al (2021) [40] highlight the importance of surveillance systems in understanding infection patterns and guiding effective IPC strategies.…”
Section: Hegarty Et Al (2019) [37]mentioning
confidence: 99%
“…In the postpandemic era, the WHO also needs to assume greater international responsibilities in this field and rebuild trust among the people to prepare for the next pandemic 51. The results of our study once again highlights the need for countries all over the world to take every opportunity to build resilient health systems and all-hazards emergency risk management based on a strong primary healthcare foundation and rebuild the health systems sustainably, more equitably and closer to communities 52…”
Section: Discussionmentioning
confidence: 72%
“…51 The results of our study once again highlights the need for countries all over the world to take every opportunity to build resilient health systems and all-hazards emergency risk management based on a strong primary healthcare foundation and rebuild the health systems sustainably, more equitably and closer to communities. 52 There are also some shortcomings in this study. First, several potential confounders, such as the objective medical conditions of participants that were not controlled because of data accessibility, may have had some impact on the results.…”
Section: Discussionmentioning
confidence: 88%
“…Kimani et al assessed IPC strategies and health facility readiness for responding to COVID-19 in Kenya, providing important data to guide IPC improvements ( 32 ). Gomes et al described initiatives to strengthen IPC in healthcare facilities in 4 countries for the prevention of healthcare-associated transmission of SARS-CoV-2 ( 33 ).…”
Section: Clinical and Health Services Delivery And Impactmentioning
confidence: 99%